Efficacy of Topical Niacinamide on Skin Hydration of Adolescents with Acne Vulgaris: An Experimental Study on the Adolescent Community in Jakarta, Indonesia - Nabila Jingga Permatasari; Tan, Sukmawati Tansil (HM Publisher, 2024)
Background: Acne vulgaris (AV) is a chronic inflammatory skin disorder common in adolescents, often accompanied by dry, irritated skin. Topical niacinamide (vitamin B3) has shown potential in increasing skin hydration and reducing AV symptoms. This study aims to evaluate the efficacy of topical niacinamide on skin hydration in adolescents with AV in Jakarta, Indonesia. Methods: This research is a randomized controlled experimental study involving 100 adolescents (14-19 years) with mild to moderate AV in Jakarta. Participants were randomly divided into two groups: the intervention group (receiving topical 4% niacinamide cream) and the control group (receiving placebo cream). The intervention was carried out for 8 weeks, and skin hydration was measured using a corneometer at baseline, week 4, and week 8. Data analysis was carried out using paired t-tests and independent t-tests. Results: There was a significant increase in skin hydration in the intervention group compared to the control group at week 4 (p < 0.001) and week 8 (p < 0.001). No significant side effects were reported. Conclusion: Topical niacinamide was effective in increasing skin hydration in adolescents with AV in Jakarta, Indonesia. This study supports the use of topical niacinamide as an adjunct therapy in the management of AV, especially in adolescents with dry, irritated skin.